On (f, ρ)−Statistical convergence and strong (f, ρ)−summability of order α - Hacer Şengül Kandemir; Mikail Et; Hüseyin Çakallı (E-Journal of Analysis and Applied Mathematics)
The main object of this article is to introduce the concepts of (f, ρ)− statistical convergence of order α and strong (f, ρ)− summability of order α of sequences of real numbers and give some inclusion relations between these spaces.